2015
DOI: 10.1002/smll.201502605
|View full text |Cite
|
Sign up to set email alerts
|

Superfast Near‐Infrared Light‐Driven Polymer Multilayer Rockets

Abstract: A gold nanoshell‐functionalized polymer multilayer nanorocket performs self‐propulsion upon the irradiation with NIR light in the absence of chemical fuel. Theoretical simulations reveal that the NIR light‐triggered self‐thermophoresis drives the propulsion of the nanorocket. The nanorocket also displays ­efficient NIR light‐triggered propulsion in ­biofluids and thus holds considerable promise for various potential biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
129
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(135 citation statements)
references
References 46 publications
3
129
0
3
Order By: Relevance
“…Unlike self‐propelled micromotors, light‐driven micromotors face a very challenging issue of achieving high velocities when moving. However, this can be accomplished using various combinations of materials with excellent catalytic performances . According to earlier research by Jang et al, Au/B/TiO 2 Janus micromotors showed multiwavelength responses from UV to visible light .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike self‐propelled micromotors, light‐driven micromotors face a very challenging issue of achieving high velocities when moving. However, this can be accomplished using various combinations of materials with excellent catalytic performances . According to earlier research by Jang et al, Au/B/TiO 2 Janus micromotors showed multiwavelength responses from UV to visible light .…”
Section: Introductionmentioning
confidence: 99%
“…By using a nanoporous polycarbonate membrane template, a tubular structure has been fabricated by layer‐by‐layer assembling negatively charged poly(styrenesulfonic acid) (PSS) and positively charged poly(allylamine hyhrochloride) (PAH) into the inner walls of the template. Au nanoparticles stabilized by citrate are deposited onto the outer or inner surface of the conical tubular structure via electrostatic interactions (Figure a) The strong absorption of plasmonic Au nanoparticles under the illumination of NIR light produces local temperature gradients, which results in the thermophoretic forces along the elongated axis of the tubular structures. The conical structure further makes the tubular nanomotors move directly toward the direction of the front small opening with a speed of up to 160 μm s −1 .…”
Section: Nanomotor Movement Control Powered By Optical Resonancesmentioning
confidence: 99%
“…Au nanoparticles stabilized by citrate are deposited onto the outer or inner surface of the conical tubular structure via electrostatic interactions (Figure a) The strong absorption of plasmonic Au nanoparticles under the illumination of NIR light produces local temperature gradients, which results in the thermophoretic forces along the elongated axis of the tubular structures. The conical structure further makes the tubular nanomotors move directly toward the direction of the front small opening with a speed of up to 160 μm s −1 . Scientists have further developed more sophisticated nanomotors to achieve a better control of the directionality of their movement.…”
Section: Nanomotor Movement Control Powered By Optical Resonancesmentioning
confidence: 99%
“…Recently, particular attraction has been given to the fuel‐free synthetic motors that are powered by various physical stimuli such as light, magnetic, and electronic field due to the adverse effect of chemical fuels such as hydrogen peroxide on the biological systems. These fuel‐free synthetic motors have reported conceptual biomedical application such as drug delivery, bone repair, photothermal therapy, and detoxification …”
Section: Introductionmentioning
confidence: 99%